Influence of Cementation and Dolomitization on Carbonate Reservoir Quality: A Literature Review - Saleh, Isman (Asosiasi Riset Ilmu Teknik Indonesia, 2026)
Carbonate reservoirs contain a substantial proportion of the world's hydrocarbon resources, yet predicting their reservoir quality remains challenging because of the complex interactions among depositional characteristics and subsequent diagenetic processes. This study presents a systematic literature review to evaluate the influence of cementation and dolomitization on the evolution of carbonate reservoir quality. Relevant studies were synthesized to examine diagenetic mechanisms, controlling factors, analytical approaches, and their impacts on porosity and permeability under different geological settings. The review indicates that dolomitization exerts both constructive and destructive effects on reservoir quality. Early replacement dolomitization commonly enhances intercrystalline porosity, improves permeability, and increases resistance to mechanical compaction, particularly in deeply buried reservoirs. Conversely, overdolomitization and pore-filling dolomite cement may significantly reduce pore connectivity. Cementation, especially by calcite, dolomite, and anhydrite, consistently acts as the principal destructive diagenetic process by occluding both primary and secondary pore systems, thereby decreasing porosity and permeability. The ultimate reservoir quality is governed by the timing, sequence, and intensity of diagenetic events, together with depositional facies, burial history, and structural controls on fluid migration. This review emphasizes that integrated petrographic, geochemical, petrophysical, and sequence-stratigraphic analyses provide the most reliable framework for predicting carbonate reservoir quality and reducing uncertainty in hydrocarbon exploration and reservoir characterization